History and Political Economy - Aspromourgos, Tony; Lodewijks, John (Routledge Studies in the History of Economics, 2004)
Impressive and authoritative, this essential book brings together a collection of essays in honour of Peter Groenewegen, one of the most distinguished historians of economic thought of a generation. His work on a wide range of economic theorists such as Adam Smith, François Quesnay and Alfred Marshall approaches a level of near insuperability.